Analisis Higher-Order Thinking Skills (HOTS) Siswa SMA pada Materi Sel - Fredy Gunawan; Asriah Nurdini Mardiyyanningsih; Hayatul Fajri (Journal on Education, 2024)
The 21st-century education focuses on developing higher-order thinking Skills (HOTS). Higher order thinking skills are a problem at SMA Negeri 1 Mempawah Hulu. For example, class XI MIA students have never conducted HOTS analysis research before. The research aimed to determine the HOTS ability of SMA Negeri 1 Mempawah Hulu students in cell material. The saturated sample used was 130 students consisting of 37 male students and 93 female students. The method used is descriptive with a quantitative approach, with research instruments in the form of essays. The first step in the research was to provide test questions which were filled in for 45 minutes. The next stage is data analysis by calculating the average student score and then calculating the percentage of HOTS scores for all students from each question indicator. The final step is to analyze the answers to each question item. Based on the results obtained, the overall HOTS ability of SMAN 01 Mempawah Hulu students in cell material is still classified as very low with an achievement percentage of 15.24%. The results obtained from each HOTS indicator were analyzed at 25.23%, evaluated at 10.46%, and created at 11.66%. The implementation of HOTS must be applied at all levels of education.